The impact of genomic neighborhood on the evolution of human and chimpanzee transcriptome - De, Subhajyoti; Teichmann, Sarah A.; Babu, M. Madan (Genome Research, 2009)
Divergence of gene expression can result in phenotypic variation, which contributes to the evolution of new species. Although the influence of trans- and cis-regulatory mutations is well known, the genome-wide impact of changes in genomic neighborhood of genes on expression divergence between species remains largely unexplored. Here, we compare the neighborhood of orthologous genes (within a window of 2 MB) in human and chimpanzee with the expression levels of their transcripts from several equivalent tissues and demonstrate that genes with altered neighborhood are more likely to undergo expression divergence than genes with conserved neighborhood. We observe the same trend when expression divergence data were analyzed from six different brain parts that are equivalent between human and chimpanzee. Additionally, we find enrichment for genes with altered neighborhood to be expressed in a tissue-specific manner in the human brain. These results suggest that expression divergence induced by this mechanism could have contributed to the phenotypic differences between human and chimpanzee. We propose that, in addition to other molecular mechanisms, change in genomic neighborhood is an important factor that drives transcriptome evolution.
10.1101/gr.086165.108